STRATEGI DAKWAH NY. HJ. MAMNUNAH RAHIEM (STUDI PADA KULIAH SUBUH DI PONDOK PESANTREN AL-AMIEN PRENDUAN) - Agus Saifuddin Amin; Laila Nur Jannah (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2023)
Strategy can be said as a mindset in planning an activity to change attitudes, opinions, and behavior of the audience. Strategy is part of communication planning. In addition, there is a policy that will determine the steps and sources used in the communication process. What is meant by wisdom here is an act that is thought in accordance with the intelligence of the communicator in compiling words. As with communication, the communicator must understand the existence of a source and interpret its destination. Likewise, a communicator must think about making the message to be conveyed so that the goal is achieved. To achieve a goal, communicators need to think about methods and techniques according to the conditions of the communicant. The communicator also needs to know every thought of the communicant, as well as the impact, what will happen because of the communication conveyed by the communicator.This study uses a qualitative approach and the type of research is descriptive analysis with interview and observation data collection methods, to obtain accurate data the researcher uses case study research. Case studies are studies that provide more valid knowledge or explore a problem in detailed terms, which have in-depth data collection, can include various sources of information.The results of this study indicate that the da'wah strategy used by Mrs. Hj. Mamnunah rahiem greatly influences other people because it has several factors, namely if we develop a strategy carefully, then a da'I will easily convey his message.